An Overview of the U.S. Bell Pepper Industry - Trina Biswas; Zhengfei Guan; Feng Wu (EDIS)
Bell pepper is one of the most widely cultivated vegetable crops in the world; it is widely grown all over the United States, and production of bell pepper has been a major economic contribution to the vegetable industry in Florida and California. This 4-page fact sheet written by Trina Biswas, Zhengfei Guan, and Feng Wu and published by the UF/IFAS Food and Resource Economics Department provides an overview of the US bell pepper industry, including production, prices, and trade. http://edis.ifas.ufl.edu/fe1028